Protein kinase C epsilon is required for non-small cell lung carcinoma growth and regulates the expression of apoptotic genes - Caino, M. Cecilia (2011)
Protein kinase C (PKC) ε, a member of the novel PKC family, plays key roles in mitogenesis and survival in normal and cancer cells. PKCε is frequently overexpressed in epithelial cancers, particularly in lung cancer. Using a shRNA approach, here we established that PKCε is required for non-small cell lung carcinoma (NSCLC) growth in vitro as well as tumor growth when inoculated into athymic mice. Moreover, sustained delivery of a PKCε selective inhibitor peptide, εV1-2, reduced xenograft growth in mice. Both RNAi depletion and pharmacological inhibition of PKCε caused a marked elevation in the number of apoptotic cells in NSCLC tumors. PKCε-depleted NSCLC cells show elevated expression of pro-apoptotic proteins of the Bcl-2 family, caspase recruitment domain (CARD)-containing proteins, and TNF ligands/receptor superfamily members. Moreover, a Gene Set Enrichment Analysis (GSEA) revealed that a vast majority of the genes changed in PKCε-depleted cells were also deregulated in human NSCLC. Our results strongly suggest that PKCε is required for NSCLC cell survival and maintenance of NSCLC tumor growth. Therefore, PKCε may represent an attractive therapeutic target for NSCLC.